Why has the crisis been bad for private pensions, but good for the flat tax? The sustainability of 'neoliberal' reforms in the new EU member states - Beblavy, Miroslav (Brussels, 2011)
"This paper examines two questions related to the sustainability of the major neoliberal, economic and social reforms in the new EU member states, namely the flat income tax and private pension pillars. First, we look at the relationship between the political consensus/controversy at the time major policy reforms were passed and the future sustainability of these reforms after a change of government."